27 Angiographic restenosis after coronary stenting in patients with previous coronary bypass surgery. (5th October 2017) - Colleran, R; Michel, J; Rheude, T; Cassese, S; Giacoppo, D; Wiebe, J; Bohner, J; Hoppmann, P; Laugwitz, K; Ibrahim, T; Kastrati, A; Byrne, R
Abstract : Introduction: Restenosis after percutaneous coronary intervention (PCI) with stent implantation in patients with prior CABG is poorly studied. The aim of this study was to investigate the incidence and predictors of angiographic restenosis after PCI in patients with and without prior CABG. Methods: Patients undergoing successful PCI of 1 or more de novo lesions with available surveillance angiography at 6–8 months after intervention were eligible for inclusion. Exclusion criteria were cardiogenic shock, renal replacement therapy and prior cardiac transplantation. Patients with prior CABG were further classified into patients who underwent bypass graft PCI versus native vessel PCI. The primary endpoint was in-segment binary restenosis at 6–8 months angiographic follow-up. Multivariate analyses were performed to adjust for differences in baseline characteristics between groups and to determine predictors of binary restenosis. Results: 10, 004 patients with 14, 999 lesions were included, 8, 803 patients (88%) without prior CABG and 1, 201 (12.0%) with prior CABG. Of patients with prior CABG, 379 (31.6%) patients had PCI to a bypass graft and 822 (68.4%) to a native vessel. A study flow diagram is shown in figure 1. Compared with patients without prior CABG, patients with prior CABG were older, had higher rates of diabetes and prior myocardial infarction, lower left ventricular ejection fraction and larger reference vessel diameter (2.95 vs. 2.85 mm, p<0.001). At 6–8 month angiographic follow-up, the rate of binary restenosis was significantly higher in patients with prior CABG compared to patients without prior CABG (25.0% vs. 20.0%, Padjusted<0.001). Among patients with prior CABG, patients with bypass graft PCI as compared to patients with native vessel PCI had a lower incidence of diabetes, a higher rate of presentation with ACS, larger target vessel size (3.42 vs. 2.80 mm, p<0.001) longer lesion length (16.0 vs. 13.9 mm, p=0.01) and significantly higher BMS use (72.1% vs. 37.0%, p<0.001). At 6–8 month angiographic follow-up, there was no significant difference in binary restenosis rates among patients with bypass graft PCI compared with those with native vessel PCI (23.8% vs. 25.3%, Padjusted=0.81). In patients with prior CABG, there was an independent association between native vessel PCI and restenosis (OR 1.47, 95% CI 1.26–1.72, p<0.001) but not bypass graft PCI and restenosis (OR 1.26, 95% CI 0.96–1.66, p=0.09) (Figure 2). Conclusions: Compared with patients without prior CABG, patients with prior CABG had overall higher rates of restenosis. In patients with prior CABG, restenosis rates were similar in patients undergoing bypass graft PCI and native vessel PCI and native vessel PCI was independently associated with binary restenosis at 6–8 months.